Diagnostic accuracy of MRI in the evaluation of adnexal masses using histopathology as the gold standard in a tertiary hospital of central Nepal - Prasad, V.Natraj (Journal of Karnali Academy of Health Sciences, 2025)
Introduction: Adnexal masses represent broad spectrum of gynecological conditions, ranging from benign cysts to malignant ovarian tumors. Accurate diagnosis and characterization are critical for clinical decision-making, including surgical planning, fertility preservation, and oncological referral. Magnetic Resonance Imaging (MRI), with superior soft-tissue contrast, multiplanar capability, and functional imaging techniques, offers improved characterization of adnexal masses. The objective of this study was to evaluate the diagnostic role of MRI in detecting and characterizing adnexal masses.Methods: A hospital-based prospective cross-sectional study was conducted among 80 female patients with adnexal masses identified on USG at the Department of Radiology, College of Medical Sciences and Teaching Hospital, Bharatpur, Chitwan, Nepal. This study was conducted between September 2024 to October, 2025. All patients went MRI evaluation followed by surgical excision and histopathological performance using (sensitivity, specificity, PPV and NPV) of MRI taking histopathology as gold standard. Data were entered and analyzed using SPSS-20. P-value